2021
DOI: 10.1097/ajp.0000000000000943
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Epidural Steroid Injections on Lumbosacral Radicular Syndrome-related Synptoms

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…Short‐ or middle‐term benefits may be valuable in patients with high levels of pain, disability and pain‐related distress. However, a recent systematic review and meta‐analysis focusing on the clinical relevance of ESI effectiveness found that only 4 of 17 studies detected clinically relevant effects, and the certainty of the evidence was either low or very low (de Bruijn et al, 2021). In a large study on the Medicare population, the rate (95% CI) of serious spinal adverse events probably associated with lumbar ESI was estimated at 5.1 (2.3 to 11.0) per one million (Eworuke et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Short‐ or middle‐term benefits may be valuable in patients with high levels of pain, disability and pain‐related distress. However, a recent systematic review and meta‐analysis focusing on the clinical relevance of ESI effectiveness found that only 4 of 17 studies detected clinically relevant effects, and the certainty of the evidence was either low or very low (de Bruijn et al, 2021). In a large study on the Medicare population, the rate (95% CI) of serious spinal adverse events probably associated with lumbar ESI was estimated at 5.1 (2.3 to 11.0) per one million (Eworuke et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Injections on Lumbosacral Radicular Syndrome-related Symptoms: Systematic Review and Meta-analysis. 2 They are of the opinion that we did not evaluate technical quality and that our systematic review (SR) includes numerous methodological and foundational weaknesses. We will respond to these comments in this letter.…”
Section: Regarding Our Study Clinical Relevance Of Epidural Steroidmentioning
confidence: 99%
“…We thank McCormick and colleagues for their thorough comments 1 to our study Clinical Relevance of Epidural Steroid Injections on Lumbosacral Radicular Syndrome-related Symptoms: Systematic Review and Meta-analysis. 2 Their comments are summarized in 4 key points, to which we will respond systematically: (1) 3 The protocol of our review was registered in PROSPERO (CRD42018115779). We included all studies that were identified with our search and fulfilled the eligibility criteria for inclusion in our review.…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%